Democratic Religion from Locke to Obama : Faith and the Civic Life of Democracy - Areshidze, Giorgi, 1983- (Book collections on Project MUSE., 2016)
Debating or making speeches, American politicians invariably cite tenets of Christian faith -- even as they unfailingly defend the liberal principles of tolerance and religious neutrality that underpin a pluralistic democracy. How these seemingly contradictory impulses can coexist -- and whether this undermines the religious tradition that makes a liberal democracy possible -- are the pressing questions that Giorgi Areshidze grapples with in this exploration of the civic role of religion in American political life. The early modern Enlightenment political philosophy of John Locke has been deeply influential -- if often misunderstood and sometimes contested -- in shaping both the theoretical and practical contours of contemporary debates and anxieties about religion in a liberal society. Areshidze demonstrates that Locke anticipated a great theological transformation of Christianity in light of modern rationalism, one that would make Christianity into a tolerant religion compatible with liberal political principles. Locke's experiment, as this book shows, has succeeded in important respects, but at a tremendous cost -- by demanding a certain theological skepticism about revealed religion that could ultimately undermine the public concern for religious or theological truth altogether. -- Provided by publisher.